Mealybugs (Hemiptera: Pseudococcidae) and their impact on the Musaceae crop - Palma-Jiménez, Melissa (2019)
Introduction. The mealybug (Hemiptera: Pseudococcidae) is known for its importance at commercial level, it can affect all stages of development on agricultural crops and cause harvest losses. Objective. The aim of this bibliographical review was to synthesize the main aspects related to taxonomy, biology, damage to host plants, geographic distribution and the impact of the mealybug on Musaceae. Development. Most of the generes have a wide geographical distribution. Can be transported during the shipment of the crop to be exported, slipping away from the phytosanitary regulations, with a high risk of introduction as a pest of economically important crops to other countries. To identify the individual at species level, adult females are used, males and nymphs lack of the necessary characteristics for their classification. Within the Pseudococcidae family, Pseudococcus elisae (Borchsenius) stands out as one of the first species identified in the Musaceae crop. The State Phytosanitary Service  of the Ministry of Agriculture and Livestock  from Costa Rica, declared by the end of 2013 and the beginning of 2014, a phytosanitary emergency due to the increase of P. elisae, however there are records of up to twenty-four species as vectors of banana streak virus, belonging to fourteen genera with different origins. The feeding period where the transmission, occurs, is associated with the mealybug species and the environmental conditions. At the same time that they inject toxins, the sugary liquids are secreted from the phloem of the plant, which serves as a means for the establishment of fungi on the surface of the attacked organsthat cause several physiological damages to the crop. Conclusion. For this reason, it is of great importance to consider related aspects to taxonomy, biology, host plants and the geographical distribution of the different species of the mealybug to develop appropriate strategies that control the pest propagation.